A re-analysis in exploring the association between temperature and COVID-19 transmissibility: an ecological study with 154 Chinese cities - Ran, Jinjun (Eur Respir J, 2020)
In this national ecological study across 154 Chinese cities, the ambient temperature was found to have a nonlinear negative association with COVID-19 transmissibility https://bit.ly/3esw8rc